KUPASAN MENGENAI PEMBUBARAN PERKAHWINAN KERANA SALAH SEORANG PASANGAN MEMELUK ISLAM OLEH AL-QARADAWI DALAM FATAWA MU’ASIRAH - Ibrahim, Basri (Jurnal Syariah, 2010)
The issue of marriage annulment because one of the spouse embraces Islam is among the new issues that draw Muslims’ attention in Malaysia lately. The opinion usually in use is the opinion of al-Shafi‘i sect which is normally known by the Muslims in Malaysia country, determining that a marriage is cancelled immediately if the couple had not performed any intercourse and cancelled after iddah, if the couple had performed intercourse. In al-Qaradawi’s analysis regarding the above issue, he referred to the debates made by Ibn Qayyim in Ahkam Ahl al-Dhimmah, because that discussion, as seen by al-Qaradawi, is stronger and the opinions selected by him are firmer and makes it easier for the women who just embraced Islam. In al-Qaradawi’s analysis in this issue it is found that the opinions of the scholars of al-Shafi‘i’s sect and other scholars in the same genre are not accurate, because of the absence of strong dalil to be refer to, on the contrary he is more prone towards the opinions of Ibn Qayyim and two other early scholar figures, namely Sayyiduna Ali k.r.m as well as the opinions of al-Zuhri. These three opinions connect a court’s roles in splitting the couple when the case is brought forward and as long as the court does not play its role, then the couple is still related as a husband and wife even though it takes a long time because of waiting for a spouse to embrace Islam.